Long-term impacts of historical education policy on wages in China: insights on over-education - Xiaodong Chen; Ding Li; Pengyu Zhu (Humanities & Social Sciences Communications)
Abstract This article contributes to the discourse on the phenomenon of over-education and its implications for labor misallocation within China. The celebrated Imperial Examination System, initiated in the Sui dynasty and enduring until 1905, cultivated an elite-driven society where educational attainments were paramount. Our study delves into historical Jinshi density data—indicative of the highest accolade in said examinations—coupled with insights from the Annual Survey of Industrial Firms. By addressing endogeneity through adjustments for reference materials and transport accessibility, we discern that prefectures exhibiting a 1% enhancement in Jinshi density per 10,000 individuals are subject to a 1030–1710 CNY wage increment presently. This increase is mainly attributed to the continuation of cultural norms influencing human capital (workers’ degree and positional title structures by gender and direct educational investments) and social capital (innovation, transport, paid-in capital structure, and welfare costs), along with migration patterns that attract talent. Our investigations further illuminate that historical examination practices incentivize ancillary advantages, encompassing welfare programs, as well as public services and amenities.